A mΘ spectrum of Reed-Muller codes. (18th August 2022) - Armand, Tsimi Jean; Cedric, Pemha Binyam Gabriel
Abstract: In this paper, we construct m Θ spectrum of Reed Muller codes, a family of m Θ linear codes [5] with large m Θ minimum distance. First, we cover the necessary material on the m Θ Boolean algebra. We then define the m Θ spectrum of Reed Muller codes RM Θ ( r, m ) as certain subspaces of the m Θ Boolean algebra . We determinate the parameters of RM Θ ( r, m ).